2017
DOI: 10.1017/s0950268817002850
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of public education on a preventable zoonotic disease: rabies

Abstract: SUMMARYEffective methods to increase awareness of preventable infectious diseases are key components of successful control programmes. Rabies is an example of a disease with significant impact, where public awareness is variable. A recent awareness campaign in a rabies endemic region of Azerbaijan provided a unique opportunity to assess the efficacy of such campaigns. A cluster cross-sectional survey concerning rabies was undertaken following the awareness campaign in 600 households in 38 randomly selected tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 33 publications
0
51
0
1
Order By: Relevance
“…Improvement in rabies awareness through the development of education campaigns has been recognised as a key factor in order to control the infection [5]. The delivery of these activities has been proven beneficial not only to provide the community with accurate information on disease prevention, but to improve their attitude concerning dog vaccination and engagement with rabies surveillance [13,45,46]. A similar regression analysis also showed that education was positively associated with the owner's intention to vaccinate their dog [44].…”
Section: Variablementioning
confidence: 99%
“…Improvement in rabies awareness through the development of education campaigns has been recognised as a key factor in order to control the infection [5]. The delivery of these activities has been proven beneficial not only to provide the community with accurate information on disease prevention, but to improve their attitude concerning dog vaccination and engagement with rabies surveillance [13,45,46]. A similar regression analysis also showed that education was positively associated with the owner's intention to vaccinate their dog [44].…”
Section: Variablementioning
confidence: 99%
“…Zoonotic diseases are diseases that can be transmitted and distributed between animals harboring the disease and humans, and having different public health burdens and it is known that 75% of emerging pathogens fall within the category of zoonotic diseases [1]. These zoonotic diseases are widely distributed in Ethiopia and include bovine tuberculosis, taeniasis, hydatidosis [2], and rabies [3]. Many zoonotic diseases are caused by organisms such as bacteria, viruses, fungi, protozoa and other parasites, with both domestic and wild animals acting as reservoirs for the pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…The application of a One Health model was introduced in educational programs for women in a brucellosis endemic region of Iran, which resulted in a significant decrease in KAP scores 1 month after short-term education courses [72]. However, in contrast, a short-term awareness campaign for rabies in Azerbaijan was not successful in demonstrating change in postexposure health-seeking behaviors [73]. These opposing results of 2 different diseases suggest that sustained longterm planning is required for a comprehensive One Health awareness and education campaign to be successful in modifying behaviors and practices.…”
Section: Public Education and Awarenessmentioning
confidence: 99%